Purchasing, Pricing, and Quick Response in the Presence of Strategic Consumers - Cachon, Gérard P.; Swinney, Robert (Management Science, 2009)
We consider a retailer that sells a product with uncertain demand over a finite selling season. The retailer sets an initial stocking quantity and, at some predetermined point in the season, optimally marks down remaining inventory. We modify this classic setting by introducing three types of consumers: myopic consumers, who always purchase at the initial full price; bargain-hunting consumers, who purchase only if the discounted price is sufficiently low; and strategic consumers, who strategically choose when to make their purchase. A strategic consumer chooses between a purchase at the initial full price and a later purchase at an uncertain markdown price. In equilibrium, strategic consumers and the retailer make optimal decisions given their rational expectations regarding future prices, availability of inventory, and the behavior of other consumers. We find that the retailer stocks less, takes smaller price discounts, and earns lower profit if strategic consumers are present than if there are no strategic consumers. We find that a retailer should generally avoid committing to a price path over the season (assuming such commitment is feasible)—committing to a markdown price (or to not mark down at all) is often too costly (inventory may remain unsold) even in the presence of strategic consumers; the better approach is to be cautious with the initial quantity and then mark down optimally. Furthermore, we discuss the value of quick response (the ability to procure additional inventory after obtaining updated demand information, albeit at a higher unit cost than the initial order). We find that the value of quick response to a retailer is generally much greater in the presence of strategic consumers than without them: on average 67% more valuable and as much as 558% more valuable in our sample. In other words, although it is well established in the literature that quick response provides value by allowing better matching of supply with demand, it provides more value, often substantially more value, by allowing a retailer to control the negative consequences of strategic consumer behavior.